ANALISIS PERBANDINGAN EFEKTIVITAS DAN KONTRIBUSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH (PAD) SEMUA KOTA DI PROVINSI SULAWESI UTARA - Sabijono, Haryanto; Tirayoh, Victorina Zusana; Datu, Christian V. (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. Local tax is a tax levied by the region based on tax regulations set by the region for the purpose of financing the local government's household. Billboard tax is one type of local tax. This study aims to determine the Effectiveness and Contribution of Billboard Tax to Local Original Revenue (PAD) of all cities in North Sulawesi Province, namely Manado City, Tomohon City, Kotamobagu City, and Bitung City. The analysis method used in this research is the analysis of the ratio of Effectiveness and Contribution, whose data is obtained from the results of interviews and documentation. The results showed that the effectiveness of billboard tax revenue from 2018-2022 at BPKAD Kotamobagu City and Bapenda Kota Bitung has been very effective, while at the Manado City Regional Revenue Office and BPKAD Tomohon City which are still ineffective in revenue billboard tax. Meanwhile, the level of billboard tax contribution to the original income of Kotamobagu City is still slightly better than Manado City, Tomohon City and Bitung City.